Development of Physics Learning Media Using Powtoon Based on Predict Observe Explain (POE) in Class XI of SMA N 6 Solok Selatan - Putri, Julia Rahma; Anaperta, Megasyani; Yanti, Iing Rika (PILLAR OF PHYSICS EDUCATION, 2024)
During the learning process, educators have used teaching materials in the form of textbooks, power points, and LKPD. After analyzing the teaching materials used by educators in the learning process, it was found that the implementation of physics learning did not apply the concept of everyday life. The learning media used by educators in the form of power points with a less attractive appearance, because there were no pictures and learning videos that linked the material being studied, this caused students to be less active during the learning process, so that the learning process that took place was still one-way. Along with the development of technology, the learning process must be able to utilize technology in its activities such as learning media. One of the learning media that can be developed is physics learning media using Powtoon which is interesting and can help students to better understand the learning process. The purpose of this study is to develop physics learning media using Powtoon based on Predict Observe Explain (POE) in class XI SMA N 6 Solok Selatan which is valid and practical. This type of research is research and development (Research and Development) which uses the 4D development model. This research was conducted in class XI IPA 3 SMA N 6 Solok Selatan which consisted of 30 students. The percentage of validity level based on material experts and media experts, obtained an average validation of 90.7% which is categorized as very valid. The level of validity of teaching materials is reviewed from the aspects of content feasibility, language feasibility, presentation feasibility and graphics. In addition, for the percentage of media practicality, an average practicality of 92.32% was obtained which was categorized as very practical.